Barriers to social participation for people with disabilities in NTD-endemic areas of Benin and Côte d'Ivoire: Assessing scope and associated factors. - Yévèdo Borel Tossou; Paule Héléna Biaka; Fifamin Noël Christelle Gbaguidi; Vignon Bedie; Sonagnon Inès Elvire Agbo; Fernand Aimé Guedou; Kouakou Jerôme Kouadio; Sèdjro Gimatal Esaï Anagonou; Franck Zinsou Mignanwande; Parfait Djossou; Brunelle Vanessa Yemadje; Flora Sylvie Houndjrebo; et al. (PLOS Global Public Health)
People with disabilities (PWDs) due to neglected tropical diseases (NTDs) or other causes experience restrictions on social participation (RSPs). This study aimed to investigate the magnitude of these restrictions and associated factors in NTD-endemic communities in Benin and Côte d'Ivoire. This cross-sectional quantitative and qualitative study was conducted from 2021 to 2022 among 841 people with disabilities (PWDs) and 90 community members and stakeholders. Questionnaires and interview guides were used for data collection. The World Health Organization P-scale score adapted to the local context, was used to assess RSPs. Univariate and multivariate analyses were performed to identify associated factors. Qualitative data were processed using triangulation or data comparison, categorized, cross-referenced, and synthesized by theme, hypothesis and indicator. Of the 841 PWDs, 65.9% had experienced RSPs. The median age (Q1; Q3) was 38 (22; 52) years, and the M/F ratio was 1.45. Of the respondents, 89.2% had a monthly income between 0 and 50,000 FCFA (76 euros); 43.7% were married, and 64.4% were uneducated. Only 98 (11.7%) were disabled due to NTDs. Factors (OR [95%IC], p-value) associated with RSPs were age (30 to 44 years (1.66 [1.06-2.59], p = 0.026), 45 to 59 years (2.26 [1.43-3.58], p = 0.001), and 60 to 74 years (2.35 [1.29-4.27], p = 0.005); Secondary/University level of education ((0.42 [0.28-0.65], p = 0.000); occupation (shopkeeper/housekeeper (0.40 [0.17-0.91]), p = 0.029), farmer (0.21 [0.11-0.40], p = 0.000), and other professions (0.44 [0.20-0.96], p = 0.038)); and income-generating activities (IGAs) (1.53 [1.06-2.22], p = 0.023). Our results demonstrate that the magnitude of RSPs among PWDs is high. The associated factors were age, education level, occupation, and IGAs.